Pharmacognostical Standardization, Phytochemical Screening and Antiulcer Activity of Terminalia bellerica - Upadhyay, Srishti; Nagar, Jagdish; Mukim, Mohammad (Asian Journal of Pharmaceutical Research and Development, 2022)
Context: Terminalia chebula Retz. (Combretaceae) is a medium-sized tree that grows in the wild throughout India. T. chebula has been extensively used in Ayurveda, Unani, and homoeopathic medicine. The fruit has been used as a traditional medicine for a household remedy against various human ailments. Traditionally T. chebula is used to cure chronic ulcer, gastritis, and stomach cancers. Objective: The present study is to evaluate the antiulcer effect of hydroalcoholic extract of Terminalia chebula fruit. Materials and methods: In the pharmacognostical, phytochemical and biological evaluation many chemicals, glassware and instruments were used. Different grades of chemicals were used as per the requirement like laboratory reagent (LR), analytical reagents (AR) and HPLC. Conclusion : The present study has been done to evaluate the antiulcer effect of METB on indomethacin induced ulcer models at various doses. The results obtained from the present study have shown that METB possesses antiulcer effect on indomethacin induced ulcers. Pre-treatment with METB particularly at a dose of 50mg/kg, 100mg/kg and 200 mg/kg decreases ulcer index, total acidity, total volume of acid secretion and increase in pH when compared with control.